2000
DOI: 10.1093/hmg/9.1.79
|View full text |Cite
|
Sign up to set email alerts
|

The sex-linked fidget mutation abolishes Brn4/Pou3f4 gene expression in the embryonic inner ear

Abstract: We have demonstrated that the phenotype of the mouse mutant sex-linked fidget ( slf ) is caused by developmental malformations of the inner ear that result in hearing loss and vestibular dysfunction. Recently, pilot mapping experiments suggested that the mouse Brn4 / Pou3f4 gene co-segregated with the slf locus on the mouse X chromosome. These mapping data, in conjunction with the observation that the vertical head-shaking phenotype of slf mutants is identical to that observed in mice with a targeted deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…A region of evolutionarily conservation was detected within a region of the human genome that is deleted in several patients with mutations in the POU3F4 gene, consistent with the hypothesis that this region is necessary for the expression of the Brn4 gene in the otic mesenchyme (Bitner-Glindzicz et al, 1995;Phippard et al, 2000). This enhancer region has been demonstrated to drive the expression of Cre recombinase in the otic mesenchyme.…”
Section: Figsupporting
confidence: 74%
See 1 more Smart Citation
“…A region of evolutionarily conservation was detected within a region of the human genome that is deleted in several patients with mutations in the POU3F4 gene, consistent with the hypothesis that this region is necessary for the expression of the Brn4 gene in the otic mesenchyme (Bitner-Glindzicz et al, 1995;Phippard et al, 2000). This enhancer region has been demonstrated to drive the expression of Cre recombinase in the otic mesenchyme.…”
Section: Figsupporting
confidence: 74%
“…This hypothesis is further supported by the sex-linked fidget allele (Pou3f4 slf ) of the gene, which is expressed in neural tube, but not the otic mesenchyme of the inner ear (Phippard et al, 2000). In this radiation-induced allele of the gene, an inversion of the central portion of the X chromosome results in a chromosomal breakpoint that lies a considerable distance upstream of the ORF, consistent with the hypothesis that an enhancer that directs expression to the otic mesenchyme lies far upstream of the ORF (Phippard et al, 2000). Mutational analyses of the human ortholog, POU3F4, demonstrated that small deletions mapping 920 kb upstream of the ORF result in a congenital hearing loss phenotype that is indistinguishable from deletions encompassing the ORF (Bitner-Glindzicz et al, 1995).…”
mentioning
confidence: 94%
“…However, sex-linked fidget (slf) mice have an inversion on the X chromosome that eliminates expression of Brn4 in the developing inner ear but not the neural tube. These mice, like one of the Brn4 knockout lines, display both cochlear and vestibular deficits (Phippard et al 2000). These results provide the first evidence that a gene, expressed primarily in the periotic mesenchyme, mediates otic epithelial morphogenesis.…”
Section: Genes Expressed In the Mesenchymementioning
confidence: 63%
“…Finally, chromosomal rearrangements may have direct positional effects. Indeed, there is experimental evidence that the rearrangements can induce changes in the expression patterns of genes located around their breakpoints (Tanimoto et al, 1999;Phippard et al, 2000;Spitz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%